Immune Protection of Rhoptry Protein 21 (ROP21) of Toxoplasma gondii as a DNA Vaccine Against Toxoplasmosis - Zhang, Zhenchao; Li, Yuhua; Wang, Mingyong; Xie, Qing; Li, Pengju; Zuo, Suqiong; Kong, Lingmin; Wang, Chenxing; Wang, Shuai (Frontiers in Microbiology, 2018)
Toxoplasma gondii （T. gondii）Rhoptry proteins (TgROPs) are the major targets as key molecules for immunodiagnosis as well as immunoprophylaxis because of their initial presentation to the host immune system. In this work, it was aimed of evaluating the protection effect of TgROP21 DNA vaccine on experimental mice subjected to T. gondii challenge. The gene sequence encoding TgROP21 was inserted into the eukaryotic expression vector pVAX I, and western blotting indicate the lysate of BHK cells transfected with pVAX-TgROP21 was specifically recognized as a band of about 82.6 kDa by serum obtained from a T. gondii infected chicken. The efficacy of intramuscular vaccination of BALB/c mice three times at weeks 0, 2 and 4 with pVAX-ROP21 was analyzed.The levels of IgG, IgG1 and IgG2a among pVAX-ROP21 vaccinated animals were integrally increased. It was uncovered by cytokine profile analyses that IFN-γ was significantly increased, while no significant changes were detected in IL-2, IL-4 and IL-10. Additionally, we found that immunization with pVAX-ROP21 significantly prolonged survival time (13.50 ± 1.65 days) after challenge infection with the virulent T. gondii RH strain, in comparison to those of control animals (died within 10 days). Moreover, the number of brain cysts (1475 ± 163) in the animals subjected to pVAX-TgROP21 vaccination decreased remarkably (P < 0.05) compared to the blank control mice (2333 ± 473), and the size of brain cysts in pVAX-TgROP21 group was significantly smaller than the groups of blank, PBS and pVAXI. It was indicated that intense cell-mediated and humoral immunity were triggered and defense against T. gondii was partially induced after vaccination by TgROP21.